Edukasi Pembuatan Rebusan Daun Salam untuk Meningkatkan Pengetahuan dalam Upaya Menurunkan Tekanan Darah pada Lansia dengan Hipertensi - Zahra Istikomah, Wakhidatus; Maryoto, Madyo; Ningrum, Ema Wahyu (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Hypertension is a condition commonly experienced by the elderly, defined as systolic blood pressure above 140 mmHg and diastolic blood pressure above 90 mmHg. Boiled bay leaves are known as one of the natural remedies that can help treat this condition. Objective: This program was implemented to provide seniors with knowledge about the benefits and methods of making bay leaf tea. Method: This activity employed both oral presentations and practical demonstrations of making bay leaf decoctions. Result: The results of the community service program showed a significant increase in the level of knowledge of the elderly, as measured by pre-tests and post-tests. In the pre-test, out of a total of 14 respondents, 8 participants (57%) had a low level of knowledge. After the intervention, the elderly participants' level of knowledge increased to 7 participants (50%) in the good category, and only 1 elderly participant (7%) remained in the poor category. Conclusion: This knowledge gain is expected to motivate older adults to use boiled bay leaves for self-managing hypertension.